The need for a subsequent transvenous system in patients implanted with subcutaneous implantable cardioverter-defibrillator - Gasperetti, Alessio; Schiavone, Marco; Vogler, Julia; Laredo, Mikael; Fastenrath, Fabian; Palmisano, Pietro; Ziacchi, Matteo; Angeletti, Andrea; Mitacchione, Gianfranco; Kaiser, Lukas; Compagnucci, Paolo; Breitenstein, Alexander; et al. (Heart rhythm, 2022)
Background - The absence of pacing capabilities may reduce the appeal of subcutaneous implantable cardioverter-defibrillator (S-ICD) devices for patients at risk for conduction disorders or with antitachycardia pacing (ATP)/cardiac resynchronization (CRT) requirements. Reports of rates of S-ICD to transvenous implantable cardioverter-defibrillator (TV-ICD) system switch in real-world scenarios are limited. - Objective - The purpose of this study was to investigate the need for a subsequent transvenous (TV) device in patients implanted with an S-ICD and its predictors. - Methods - All patients implanted with an S-ICD were enrolled from the multicenter, real-world iSUSI (International SUbcutaneouS Implantable cardioverter defibrillator) Registry. The need for a TV device and its clinical reason, and appropriate and inappropriate device therapies were assessed. Logistic regression with Firth penalization was used to assess the association between baseline and procedural characteristics and the overall need for a subsequent TV device. - Results - A total of 1509 patients were enrolled (age 50.8 ± 15.8 years; 76.9% male; 32.0% ischemic; left ventricular ejection fraction 38% [30%-60%]). Over 26.5 [13.4-42.9] months, 155 (10.3%) and 144 (9.3%) patients experienced appropriate and inappropriate device therapies, respectively. Forty-one patients (2.7%) required a TV device (13 bradycardia; 10 need for CRT; 10 inappropriate shocks). Body mass index (BMI) >30 kg/m2 and chronic kidney disease (CKD) were associated with need for a TV device (odds ratio [OR] 2.57 [1.37-4.81], P = .003; and OR 2.67 [1.29-5.54], P = .008, respectively). - Conclusion - A low rate (2.7%) of conversion from S-ICD to a TV device was observed at follow-up, with need for antibradycardia pacing, ATP, or CRT being the main reasons. BMI >30 kg/m2 and CKD predicted all-cause need for a TV device.
Online veröffentlicht: 30 June 2022, Artikelversion: 28 November 2022
Gesehen am 05.06.2023